Exploiting the power of UPLC in separation and simultaneous determination of pholcodine, guaiacol along with three specified guaiacol impurities - Hager M. Mohamed; Hala E. Zaazaa; M. Abdelkawy; Mahmoud A. Tantawy (BMC Chemistry, 2023)
Abstract Pholcodine and guaiacol are widely used together in pharmaceutical syrups for cough treatment. On the other hand, the Ultra Performance Liquid Chromatographic technique is characterized by having the power of increasing chromatographic efficiency and decreasing run time compared to the traditional High Performance Liquid Chromatographic one. In this work, this power was exploited for the simultaneous determination of pholcodine, guaiacol along with three guaiacol impurities, namely; guaiacol impurity A, guaiacol impurity B, and guaiacol impurity E. Good separation was achieved by employing Agilent Zorbax C8 column (50 × 2.1 mm) as the stationary phase, and acetonitrile: phosphate buffer pH 3.5 (40: 60, by volume) as a mobile phase. The proposed method was validated as per International Council for Harmonisation guidelines. Linear relationships, at ranges of 50–1000 µg mL−1 for pholcodine and 5–100 µg mL−1 for guaiacol and the three related impurities, were established. Finally, the proposed method was applied for pholcodine and guaiacol determination in Coughpent® syrup and compared favorably to the reported one.